DEVELOPMENT OF WEB-BASED LEARNING MEDIA - Anna Laila Istifaroh (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
The purpose of this research is to design, create, and develop web-based learning media that utilizes the use of the internet in the form of Browser Based Training learning media in the form of CD (Compact Disk) to assist learning. The type of research used in this research is a prototype experiment, while the focus of the research is how to design, create, and test E-Learning learning media based on Training. In general, the educational criteria of this program are included in good criteria and in accordance with the applied curriculum.Keywords: Learning Media, Browser-Based Training, Manual Transmission